Internalisasi Inspirational Motivation Kepala Madrasah Dalam Mengembangkan Budaya Organisasi Berprestasi - Mahmud Mahmud (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
The purpose of this study was to analyze the inspirational motivation internalized by the principal in developing a high-achieving organizational culture in his institution. This qualitative research with a phenomenological approach was conducted at MI Muslimat NU Pucang Sidoarjo. Sources of data are school principals, teachers, education staff, student guardians, and students. Collecting data by in-depth interviews, participant observation, and documentation. Data analysis was performed by data reduction, data display, and data verification. Internalization of the headmaster's inspirational motivation in developing a high-achieving organizational culture in madrasah, seen in: making himself an example, convincing communication, inviting change and improvement, displaying an interesting vision and mission, giving meaning to work, campaigning for action, understanding opportunities and opportunities and intelligently handle it, leaders don't get caught up in the mainstream.